2014
DOI: 10.1038/jhh.2013.129
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic risk factors and masked hypertension in the general population: the Finn-Home study

Abstract: The association between masked hypertension and metabolic syndrome (MS) or insulin resistance is unclear. We investigated an untreated nationwide population sample (n = 1582, age 44-74 years). Duplicate office blood pressure (BP) measurements were taken on one visit and duplicate morning and evening home measurements were taken for 7 days. Masked hypertension was defined as office BP < 140/90 mm Hg with home BP ⩾ 135/85 mm Hg. Logistic regression analysis was used to determine the association between masked hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
5
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
1
18
5
4
Order By: Relevance
“…46 Equally, some participants with true hypertension may have been misclassified as normotensive, often termed 'masked hypertension'. 47 Masked hypertension is estimated to occur in 8-23% of those with normal BP readings, 48 resulting in an underestimate of the prevalence of hypertension in this study. White coat hypertension and masked hypertension create difficulties in classifying hypertension based on single BP readings, as a result a minimum of two readings are required for epidemiological studies 15 and current clinical guidelines recommend ambulatory BP measurement to confirm a diagnosis of hypertension.…”
Section: Limitations Of the Studymentioning
confidence: 79%
“…46 Equally, some participants with true hypertension may have been misclassified as normotensive, often termed 'masked hypertension'. 47 Masked hypertension is estimated to occur in 8-23% of those with normal BP readings, 48 resulting in an underestimate of the prevalence of hypertension in this study. White coat hypertension and masked hypertension create difficulties in classifying hypertension based on single BP readings, as a result a minimum of two readings are required for epidemiological studies 15 and current clinical guidelines recommend ambulatory BP measurement to confirm a diagnosis of hypertension.…”
Section: Limitations Of the Studymentioning
confidence: 79%
“…14,15 Finally, the presence of metabolic syndrome, diabetes mellitus, chronic kidney disease, shortened sleep time, or obstructive sleep apnea may predispose to masked hypertension largely because of nocturnal hypertension. [16][17][18][19][20] Indeed, elevated nighttime BP and nondipping or rising nocturnal BP patterns, with or without elevated daytime ABPM values, may be associated with normal conventional office BP values, and hence with a diagnosis of masked hypertension. [20][21][22] In summary, there is a need for 24-hour ABPM with assessment of both day and nighttime BP to diagnose masked hypertension in the many conditions where it might occur.…”
Section: Conditions In Which Maskedmentioning
confidence: 99%
“…[34][35][36][37] Importantly, a meta-analysis done by Hodgkinson et al 38 concluded that neither office nor HBPM had sufficient sensitivity nor specificity to replace ABPM as the reference standard. A further advantage of ABPM over HBPM is the ability to identify patients with normal daytime but nocturnal masked hypertension.…”
Section: Diagnostic Strategies For Masked Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations